1988
DOI: 10.1289/ehp.88789
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of blood lead levels to blood pressure in the U.S. population.

Abstract: Numerous observations have indicated a relationship between moderate or heavy lead exposure and high blood pressure. To determine whether low-level lead exposure is related to blood pressure in the U.S. population, we analyzed data from the National Health and Nutrition Examination Survey II for persons 12 to 74 years of age. Significant correlations were found between blood lead and blood pressure for each race-gender group, and blood lead levels were significantly higher in groups with high diastolic blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(56 citation statements)
references
References 19 publications
5
51
0
Order By: Relevance
“…Although significant progress has occurred regarding environmental contamination, there are still serious problems produced by heavy metals. The positive correlation between the concentration of plasma lead and hypertension (37,38), one of the most prominent cardiovascular problems in many countries, and the increase in all causes of lead-related deaths, including circulatory and cancer mortality (39) reinforce the biological significance of lead as an important hazard.…”
Section: Discussionmentioning
confidence: 99%
“…Although significant progress has occurred regarding environmental contamination, there are still serious problems produced by heavy metals. The positive correlation between the concentration of plasma lead and hypertension (37,38), one of the most prominent cardiovascular problems in many countries, and the increase in all causes of lead-related deaths, including circulatory and cancer mortality (39) reinforce the biological significance of lead as an important hazard.…”
Section: Discussionmentioning
confidence: 99%
“…Although significant progress has occurred regarding environmental contamination, there are still serious problems produced by heavy metals. The positive correlation between plasma lead concentration and hypertension (6)(7)(8), one of the most prominent cardiovascular problems in many countries, and the increase of all-cause mortality, including circulatory and cancer mortality (5), reinforce the biological significance of lead as an important hazard.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research reported that exposure to low levels of lead causes hypertension in animals and humans (6,7). Analyzing data from the Third National Health and Nutrition Examination Survey (NHANES, 1988(NHANES, -1994, a positive correlation was reported between plasma lead concentration and arterial pressure in black men and women (8).…”
Section: Introductionmentioning
confidence: 96%
“…It is noteworthy that some large studies, which supported a positive relationship between blood pressure and blood lead, based their conclusions on a single blood pressure reading. 42,58 Some reports based on the NHANES II Study (1976)(1977)(1978)(1979)(1980) showed a relationship between blood pressure and blood lead concentration that was particularly strong among white middle-aged men. 69 However, the quality of the blood pressure measurements was questionable.…”
Section: Discussionmentioning
confidence: 99%